Transgression et « mauvais genre » dans cinq romans de George Meredith (1828-1909) - Marina Poisson (Cahiers Victoriens et Edouardiens)
This article aims at exploring the notion of ‘mauvais genre’ in five novels of George Meredith (The Ordeal of Richard Feverel, 1859; Evan Harrington, 1860; The Adventures of Harry Richmond, 1871; Beauchamp's Career, 1875; Diana of the Crossways, 1885). ‘Mauvais genre’ takes on three meanings: a social transgression (something or someone looking disreputable), a sexual subversion (of gender) or a textual one (affecting the genre of the novel). The ‘mauvais genre’ is first considered as a mistake taking the shape of a ‘wrong’ style, behaviour, gender or genre, momentarily deviating from the (Victorian) norm: transgression is thus understood as mere digression, which is soon to be ousted by the social or textual norms and habits maintaining the status quo of social classes, gender behaviour or literary genre. But the ‘mauvais genre’ is then analysed as part and parcel of the aesthetics, ethics and poetics of George Meredith: transgression, transsexuality and transtextuality seem to go hand in hand. As an appeal to social, political and poetical innovation, the ‘mauvais genre’ calls for otherness and newness, creation and procreation, as it gives birth to new norms, which are no longer ‘wrong’ or ‘bad’ but ‘novel’. Social, genre and gender transgressions ultimately become synonymous with transformation and (re)generation.